Structures and stabilities of alkaline earth metal peroxides XO sub(2) (X = Ca, Be, Mg) studied by a genetic algorithm - Zhao, Xin; Nguyen, Manh Cuong; Wang, Cai-Zhuang; Ho, Kai-Ming (RSC advances, 2013)
The structures and stabilities of alkaline earth metal peroxides XO sub(2) (X = Ca, Be, Mg) were studied using an adaptive genetic algorithm (GA) for global structure optimization in combination with first-principles calculations. From the adaptive GA search, we obtained an orthorhombic structure for CaO sub(2) with 12 atoms in the unit cell, which is energetically more favorable than the previously proposed structures. Reaction energy of the decomposition CaO sub(2) arrow right CaO + 1/2O sub(2) determined by density functional theory (DFT) calculation shows that this orthorhombic calcium peroxide structure is thermodynamically stable. The simulated X-ray diffraction (XRD) pattern using our predicted structure is in excellent agreement with experimental data. We also show that crystal phase BeO sub(2) is unlikely to exist under normal conditions. MgO sub(2) has a cubic pyrite structure, but it is not stable against decomposition: MgO sub(2) arrow right MgO + 1/2O sub(2).